Hotel crimes: An unexplored victimization in the hospitality industry. Issue 4 (October 2017) - Ho, Taiping; Zhao, Jinlin; Dooley, Brendan
Abstract The nature of hotel crimes can be generally regarded as opportunistic and convenient. The hospitality industry is particularly sensitive to criminal activities in tourist destinations. The present researchers have reviewed all reports of hotel/motel incidents in the Miami-Dade County and reported to Miami-Dade Police Department (MDPD) during the period of 1 January 2006–31 December 2010. A review of MDPD hotel-related incident reports (N =997) revealed patterns of hotel crimes and the effects of hotel guests' characteristics on a variety of hotel-related victimizations. This study results indicated that a vast majority of hotel crimes were property-related; only 5 hotel-related incidents were reported to the police, which were classified as crime against person such as armed robbery or physical assault. This study also found that there were three major criminal activities carried out against hotel guests at the hotel settings – theft, burglary and car break-in. Nonetheless, the suspect's characteristics were virtually unknown on MDPD hotel-related incident reports.